Methyl-Cantharidimide (MCA) Has Anticancer Efficacy in ABCB1- and ABCG2-Overexpressing and Cisplatin Resistant Cancer Cells - Li, Yi-Dong; Mao, Yong; Dong, Xing-Duo; Lei, Zi-Ning; Yang, Yuqi; Lin, Lizhu; Ashby, Charles R.; Yang, Dong-Hua; Fan, Ying-Fang; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
In this study, we revealed that the efficacy of methyl-cantharidimide (MCA), a cantharidin (CTD) analog, as an anticancer drug in ABCB1, ABCG2 overexpressing cancer multidrug resistance (MDR) cells and in cisplatin resistant cancer cells. The results indicated that: (i) MCA was efficacious in the ABCB1-overexpressing MDR cell line, KB-C2, and the ABCB1-gene-transfected cell line, HEK293/ABCB1 (IC50 from 6.37 to 8.44 mM); (ii) MCA was also efficacious in the ABCG2-overexpressing MDR cell line, NCI-H460/MX20, and the ABCG2-gene-transfected cell lines, HEK293/ABCG2-482-R2, HEK293/ABCG2-482-G2, and the HEK293/ABCG2-482-T7 cell lines (IC50 from 6.37 to 9.70 mM); (iii) MCA was efficacious in the cisplatin resistant cancer cell lines, KCP-4 and BEL-7404/CP20 (IC50 values from 7.05 to 8.16 mM); (iv) MCA (up to 16 mM) induced apoptosis in both BEL-7404 and BEL-7404/CP20 cancer cells; (v) MCA arrested both BEL-7404 and BEL-7404/CP20 cancer cells in the G0/G1 phase of the cell cycle. (vi) MCA upregulated the expression level of the protein, unc-5 netrin receptor B (UNC5B) at 8 mM concentration in HepG2 and BEL-7404 cancer cells. Overall, our results declaimed that MCA’s efficiency in ABCB1- and ABCG2-overexpressing and cisplatin resistant cancer cells is due to its function in inducing apoptosis and cell cycle arrest in the G0/G1 phase.